Ordenamiento territorial o el arte de vivir en comunidad - Gómez Espinoza, Nelson (2005)
In this paper I present a synthesis of what is understood for territorial management and its different stages when applied to specific cases. It departs from the concept that territorial management is not only a technical, economic, and political issue bur also a cultural one, where the value systems play a very important role, because each society arranges its space according to its culture. Only by this way we may reach asustainable territorial management.